1999
DOI: 10.1038/sj.ejcn.1600855
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of a monounsaturated fat diet and a high carbohydrate diet on cardiovascular risk factors in first degree relatives to type-2 diabetic subjects

Abstract: Results: Similar lowering effects on total cholesterol, low density lipoprotein (LDL)-cholesterol, triglyceride and apoB levels were seen after the two diets. Slightly higher levels of high-density lipoprotein (HDL)-cholesterol (1.4 AE 0.4 vs 1.3 AE 0.4 mmolal, P`0.0001) and apoA-1 (1.2AE 0.3 vs 1.1 AE 0.3 mmolal, P`0.05) were found in the MUFA-diet. Furthermore, the insulin sensitivity, as assessed by Bergman's minimal model, and the ®rst response insulin areas were similar, as were the 24-h blood pressures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 41 publications
1
23
1
1
Order By: Relevance
“…Several studies appear to have corroborated these data, and a metaanalysis has shown that compared with carbohydrates, MUFA improve both the lipid profile and the glycemic index, with similar levels of basal insulin and glycated haemoglobin [47]. Since then, a number of clinical trials have produced various results, in that they have not always confirmed differences in either glycemic control or the lipid profile, either in patients or in persons at high risk of developing type 2 diabetes [48][49][50]. A study performed by our group on a sample of healthy young adults found no differences in peripheral sensitivity to insulin following the ingestion of MUFA-rich and carbohydrate-rich diets [51].…”
Section: Olive Oil and Cardiovascular Risk Factorsmentioning
confidence: 89%
“…Several studies appear to have corroborated these data, and a metaanalysis has shown that compared with carbohydrates, MUFA improve both the lipid profile and the glycemic index, with similar levels of basal insulin and glycated haemoglobin [47]. Since then, a number of clinical trials have produced various results, in that they have not always confirmed differences in either glycemic control or the lipid profile, either in patients or in persons at high risk of developing type 2 diabetes [48][49][50]. A study performed by our group on a sample of healthy young adults found no differences in peripheral sensitivity to insulin following the ingestion of MUFA-rich and carbohydrate-rich diets [51].…”
Section: Olive Oil and Cardiovascular Risk Factorsmentioning
confidence: 89%
“…The wash-out period between the two challenge tests was at least 2 days. On study days, blood samples were taken at t = 0 (≥ 10 h of fasting) and six time points (t = 0.5, t = 1, t = 2, t = 4, t = 6, and t = 8 h) after consumption of the challenge drinks for analysis of a total of 132 different metabolic markers on the results of previous studies with a similar study design [6,[19][20][21]. To minimize the risk of bias and enhance the validity of statistical comparisons, we choose to only include male subjects in this explorative study.…”
Section: Methodsmentioning
confidence: 99%
“…The comparisons were made under isoenergetic conditions, with the bulk of the remaining energy provided by varying carbohydrate, protein remaining fairly constant, and insulin sensitivity assessed by means of a clamp or frequent-sampling intravenous glucose tolerance test. In 6 of the 11 studies (34,35,(39)(40)(41)(42), there were no appreciable differences in insulin sensitivity on the high-and low-fat diets. Four studies suggested reduced sensitivity on the high-fat diets, but in these the percentage of energy from fat was extreme, as was the intake of saturated fat (33,36,37,43).…”
Section: Dietary Fatmentioning
confidence: 99%